Plato on Virtuous Leadership: An Ancient Model for Modern Business - Bauman, David C. (Business ethics quarterly, 2018)
The business ethics and leadership literature has paid little attention to the analysis of virtue in the Socratic dialogues, but Plato’s account of virtue and persuasion offer relevant insights for business leaders. In the Republic, Plato’s description of five types of leaders offers a new perspective on leadership selection and development using the moral psychology of both virtuous and non-virtuous leaders. In this article, I explain Plato’s account of virtue and knowledge, his three-part moral psychology, the four cardinal virtues that virtuous leaders develop, and his continuum of five leader types. I apply Plato’s model to leadership issues in today’s corporate world and explain how the model can guide leaders, board members, and investors.